Freezing the Bioactive Conformation to Boost Potency: The Identification of BAY 85‐8501, a Selective and Potent Inhibitor of Human Neutrophil Elastase for Pulmonary Diseases. Issue 7 (17th June 2015) - von Nussbaum, Franz; Li, Volkhart M.‐J.; Allerheiligen, Swen; Anlauf, Sonja; Bärfacker, Lars; Bechem, Martin; Delbeck, Martina; Fitzgerald, Mary F.; Gerisch, Michael; Gielen‐Haertwig, Heike; Haning, Helmut; Karthaus, Dagmar; et al.
Abstract Human neutrophil elastase (HNE) is a key protease for matrix degradation. High HNE activity is observed in inflammatory diseases. Accordingly, HNE is a potential target for the treatment of pulmonary diseases such as chronic obstructive pulmonary disease (COPD), acute lung injury (ALI), acute respiratory distress syndrome (ARDS), bronchiectasis (BE), and pulmonary hypertension (PH). HNE inhibitors should reestablish the protease–anti‐protease balance. By means of medicinal chemistry a novel dihydropyrimidinone lead‐structure class was identified. Further chemical optimization yielded orally active compounds with favorable pharmacokinetics such as the chemical probe BAY‐678. While maintaining outstanding target selectivity, picomolar potency was achieved by locking the bioactive conformation of these inhibitors with a strategically positioned methyl sulfone substituent. An induced‐fit binding mode allowed tight interactions with the S2 and S1 pockets of HNE. BAY 85‐8501 ((4S)‐4‐[4‐cyano‐2‐(methylsulfonyl)phenyl]‐3, 6‐dimethyl‐2‐oxo‐1‐[3‐(trifluoromethyl)phenyl]‐1, 2, 3, 4‐tetrahydropyrimidine‐5‐carbonitrile) was shown to be efficacious in a rodent animal model related to ALI. BAY 85‐8501 is currently being tested in clinical studies for the treatment of pulmonary diseases.